Microwave-Synthesized Multicomponent Nanoparticle-Drug Combinations as Selective Adjuvants for Proton Therapy in Non-Small Cell Lung Cancer - David Aphkhazava; Babry Oren; Archil Chirakadze; Nodar Mitagvaria; Neli Makhviladze; Marina Devdariani; Irina Bedinashvili; Mzia Tsiklauri; Manana Makharadze; Nodar Sulashvili; Priyanka Haibat Khadake; Tanvi Naresh Patil; et al. (Theoretical Hypotheses and Empirical Results, 2026)
Non-small cell lung cancer remains the principal contributor to lung-cancer mortality worldwide, and durable local control continues to be constrained by the need to protect the surrounding thoracic organs while overcoming tumor-specific resistance mechanisms. Proton therapy offers a compelling physical solution because the Bragg peak permits steep dose fall-off and reduced exit dose, but the biological effectiveness of treatment in non-small cell lung cancer is still limited by heterogeneity in redox state, DNA-damage repair capacity, hypoxia, and stromal protection. The present manuscript describes a proton-therapy-oriented preclinical platform based on microwave-synthesized copper oxide and zinc oxide nanodispersions combined with clinically familiar drug backbones, especially gemcitabine plus cisplatin and carboplatin plus paclitaxel. Selectivity was examined by comparing A549 non-small cell lung cancer cells with normal human dermal fibroblasts, and biological effects were quantified by MTT viability testing together with Annexin V-FITC/propidium iodide analysis of apoptosis and necrosis. Acute translational safety was further explored in chick embryos and Wistar rats. Across the tested multicomponent formulations, cancer-cell selectivity increased by approximately 3- to 7-fold relative to conventional components used alone while preserving the existing safety profile, and the strongest gemcitabine-cisplatin-centered combinations exceeded gemcitabine control by 8.7- to 15.2-fold. These findings are mechanistically consistent with literature showing that oxide nanoparticles can intensify oxidative stress, ion imbalance, mitochondrial dysfunction, and DNA injury, thereby magnifying the effectiveness of established antitumor regimens in biologically vulnerable tumor cells. The broader thoracic-oncology literature supports the translational rationale for this approach because proton therapy can substantially improve dose shaping in lung cancer, yet still benefits from selective biological intensification, and contemporary nanomedicine studies continue to highlight radiosensitization, metal-based enhancement, iron-oxide multifunctionality, boron-oriented proton concepts, and receptor-guided delivery as promising routes for improving therapeutic ratio. Taken together, the data support microwave-synthesized nanoparticle-drug combinations as a practical and scalable strategy for selective intensification of future proton-based treatment in non-small cell lung cancer, while also identifying the next developmental priorities as receptor-targeted uptake, mechanistic biomarker validation, rigorously specified proton-irradiation experiments, and advanced in vivo efficacy studies.